Intracranial pressure following decompressive hemicraniectomy for malignant cerebral infarction: clinical and treatment correlations - Funchal, Bruno Ferreira; Alves, Maramélia Miranda; Suriano, Ítalo C.; Chaddad-Neto, Feres Eduardo; Ferraz, Maria E. M. R.; Silva, Gisele Sampaio (Arquivos de Neuro-Psiquiatria, 2018)
Decompressive craniectomy (DC) reduces mortality and improves outcome in patients with massive brain infarctions. The role of intracranial pressure (ICP) monitoring following DC for stroke has not been well established.Methods: We evaluated 14 patients admitted to a tertiary hospital with malignant middle cerebral artery infarctions, from October 2010 to February 2015, who underwent DC and had ICP monitoring. Patients with and without episodes of ICP elevation were compared.Results: Fourteen patients were submitted to DC and had ICP monitoring following the procedure during the period. Ten patients (71.4%) had at least one episode of sustained elevated ICP in the first seven days after surgery. Maximal ICP levels had no correlation with age, time to hemicraniectomy or Glasgow Coma Scores at admission, but had a trend toward correlation with the National Institutes of Health Stroke Scale score at admission (p = 0.1). Ventriculitis occurred in 21.4% of the patients.Conclusions: High ICP episodes and ventriculitis were common in patients following hemicraniectomy for malignant middle cerebral artery strokes. Therefore, the implications of ICP and benefits of the procedure should be firmly established.
Keywords: cerebral infarction; decompressive craniectomy; intracranial pressure